2019
DOI: 10.1371/journal.pone.0217383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylphenidate on the ERP amplitude in youth with ADHD: A double-blind placebo-controlled cross-over EEG study

Abstract: Methylphenidate (MPH) is a first line drug for attention-deficit/hyperactivity disorder (ADHD), yet the neuronal mechanisms underlying the condition and the treatment are still not fully understood. Previous EEG studies on the effect of MPH in ADHD found changes in evoked response potential (ERP) components that were inconsistent between studies. These inconsistencies highlight the need for a well-designed study which includes multiple baseline sessions and controls for possible fatigue, learning effects and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Examining each time window separately, MFT changes were most evident immediately following stimulus presentation ('early') and in preparation for the upcoming task trial ('late'), although it should be noted that we did not observe a formal statistical interaction between session and time window for these analyses. Early processing (approximately 100 ms post-stimulus presentation) is thought to reflect initial orienting of attentional resources [41][42][43], while late processing (approximately 650-800 ms post-stimulus presentation) may reflect post-response processes, such as suppressing the previous stimulus and updating in preparation for the upcoming trial [26]. With respect to the present study, children with ADHD have shown impaired neural oscillations for both early and late stimulus processing [26].…”
Section: Plos Onementioning
confidence: 47%
See 1 more Smart Citation
“…Examining each time window separately, MFT changes were most evident immediately following stimulus presentation ('early') and in preparation for the upcoming task trial ('late'), although it should be noted that we did not observe a formal statistical interaction between session and time window for these analyses. Early processing (approximately 100 ms post-stimulus presentation) is thought to reflect initial orienting of attentional resources [41][42][43], while late processing (approximately 650-800 ms post-stimulus presentation) may reflect post-response processes, such as suppressing the previous stimulus and updating in preparation for the upcoming trial [26]. With respect to the present study, children with ADHD have shown impaired neural oscillations for both early and late stimulus processing [26].…”
Section: Plos Onementioning
confidence: 47%
“…Here, we focused on post-stimulus ERSP changes in peak MFT, as in our previous work [18]. In addition to peak MFT, other work has pointed to the relevance of early and late EEG-based components in populations with cognitive control and attentional difficulties, such as ADHD [26][27][28][29]. To examine potential timing differences across the 0-880 ms time course, we created 120 ms composite bins at 3 timepoints during the trials: (1) the first three windows ('early': 0-120 ms), (2) the three windows around the MFT peak ('peak': 160-280 ms, as the peak time bin was found to be 200-240 ms, see Results), and (3) the last three windows ('late': 760-880 ms).…”
Section: Primary Outcome Metric: Neural Assessment Of Attentional Controlmentioning
confidence: 99%
“…Regarding specifically visual inhibition tasks, atypical N2 and P3 have been widely described in children and adolescents (Doehnert et al., 2010; Groom et al., 2008, 2010; Johnstone & Clarke, 2009; Rubinson et al., 2019). Although debate persists, N2 is considered to be related to early inhibition control (Falkenstein et al., 1999; Sur & Sinha, 2009) and more specifically to conflict monitoring (Albares et al., 2015; Donkers & van Box tel, 2004; Enriquez‐Geppert et al., 2010; Huster et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most robust ERP alterations have been reported in early orienting, memory encoding, inhibitory control, and error‐processing components in children with ADHD compared with typically developing children (TDC; Barry et al., 2003; Johnstone et al., 2013; Kaiser et al., 2020; Lenartowicz et al., 2014, 2019). Because inhibition control has been considered as the primary deficit in ADHD (Barkley, 1997), measures of inhibition processes like GO/NoGO tasks were extensively used to investigate EEG features of ADHD (Baijot et al., 2016, 2017; Buchmann et al., 2011; Groom et al., 2010; Johnstone & Clarke, 2009; Rubinson et al., 2019; Wiersema et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…One of the more popular environments used for preprocessing is MATLAB software together with open packages, i.e., EEGLAB, ERPLAB [20], SPM or Fieldtrip, or commercial ones, i.e., Curry or BESA. The aforementioned filters have been widely described in scientific papers both in technical terms, FIR [21,22], IIR [23,24], FFT [25,26], NOTCH, and in clinical applications or in typical research, FIR [27], NOTCH [28], FFT [29].…”
Section: Introductionmentioning
confidence: 99%